Determination of Employee Works Performance through Employee Works Motivation with Organizational Support as a Moderating Variable at PT. MEITECH EKA BINTAN - Endra Teja Kesuma; Chablullah Wibisono; Bambang Satriawan (Journal of Comprehensive Science, 2026)
This study investigates the determinants of employee performance at PT Meitech Eka Bintan by examining the roles of organizational culture, employee competence, employee commitment, work environment, and work motivation, with organizational support positioned as a moderating variable. The research is grounded in organizational theory and human resource performance frameworks, emphasizing the strategic importance of motivation and support systems in a heavy fabrication industry context characterized by high turnover. The objective is to analyze both direct and indirect relationships among variables and to evaluate the mediating role of work motivation as well as the moderating function of organizational support. A quantitative approach was employed using questionnaires distributed to 220 engineers, supervisors, and craftsmen. Data were analyzed using SmartPLS 4.1 with validity, reliability, and structural model testing. The results indicate that work motivation significantly influences employee performance and partially mediates the relationship between work environment and performance. Organizational culture and competence directly affect performance, while commitment influences performance indirectly through motivation. Organizational support significantly strengthens the relationship between motivation and performance but does not moderate motivation formation. In conclusion, employee performance in this industry is driven primarily by motivation and a supportive organizational system rather than by culture or commitment alone.